Tapentadol in the treatment of osteoarthritis: pharmacological rationale and clinical evidence - Rinonapoli, Giuseppe (J Pain Res, 2019)
Osteoarthritis (OA) is the most prevalent joint disease in older people worldwide. Pain owing to OA is considered one of the most frequent causes of chronic pain; however, current pharmacological approaches have some limitations in terms of efficacy and safety. Of note, descending inhibitory pain pathways are often disrupted in chronic OA pain, and pharmacotherapies targeting those pathways – eg, those that block norepinephrine reuptake may be more appropriate for managing chronic pain than pure μ-opioid receptor (MOR) agonists. Tapentadol is an analgesic molecule, which combines two synergistic mechanisms of action, MOR, and norepinephrine reuptake inhibition. This narrative review will briefly discuss the mechanisms contributing to the onset and maintenance of pain in OA patients; clinical data on the use of tapentadol in this setting will then be presented and commented.